Agricultura familiar e transições sociotécnicas: a produção de novidades nas agroindústrias familiares - Dengo, Mariana Beal (2018)
The general objective of this research was to identify and analyze the production of novelties in family agroindustries, evidencing their effects on rural families and the processes of socio-technical transitions that occur in the agrifood system. In order to identify the novelties generated in the production systems with agroindustries, how they were becoming historically, the knowledge used and the changes provided. Three research questions emerged: a) How does the historical construction of novelties in family agroindustries occur? b) What are the types and characteristics of novelties developed by family agroindustries? c) What socio-technical transitions occur in the food system and in the regional development from the novelties built by the family agroindustries? The study was carried out in the Municipality of Verê - Southwest Region of Paraná, where agroindustrial initiatives are varied and produces innovative effects at the local level. The study took as its theoretical basis the Actor-Oriented Perspective (POA) and the Multi-Level and Coevolutionary Perspective (PMN), through which social actors have agency capacity and produces different types of novelties and sociotechnical transitions. The methodology followed the theoretical orientation of the POA and raised primary and secondary data in qualitative and quantitative way. Data were collected through semi-structured interviews, photographs, observations and field diary. Four farmers were interviewed with family agroindustries and eight technicians directly involved with food processing in the municipality. The main results obtained show that agroindustries generate productive and technological innovations that farmers have developed along trajectories through scientific, tacit and contextual knowledge. Environmental innovations have also been found to favor the protection of the environment where farmers are inserted and the awareness of those who consume more sustainable food. On the other hand, organizational innovations favor the production and marketing of food from family farms and the collective action of farmers and social organizations. In addition, the market novelties analyzed shows that agroindustries sell through short chains and use government programs (PAA and PNAE) to make their sales viable. As a result, the novelties made possible the permanence of their families in rural areas. Often the novelties arise in the system of production of raw materials, but later contribute directly and indirectly to agroindustrial activities. The novelties provided socio-technical transitions that positively impacted on economic, social and environmental aspects. However, the novelties are still at the sociotechnical niche level, modifying only the reality of the social actors involved and some minor changes in the regime. For this reason, the creation of novelties in family agroindustries deserve greater attention in order to enable new sociotechnical transitions with greater comprehensiveness in agrifood systems and processes of regional and rural development.